(untitled) (Jalalabad Medical Journal, 2025)
A rare case of patent vitellointestinal duct along with patent urachus in an 8 months old male baby is reported here, who presented with umbilical discharge and swelling of the umbilicus since the separation of the umbilical cord. Our initial diagnosis was umbilical adenoma. On exploration, the umbilicus was connected to the ileum and the apex of the urinary bladder through two communicating channels. The urachus was completely excised after ligation, the patent vitellointestinal duct was resected and the ileum anastomosed. Jalalabad Med J 22; 19 (1): 31-34